Dietary Supplement Use in Australian Army Personnel. Issue 5 (27th October 2018) - Kullen, Charina; Prvan, Tania; O'Connor, Helen
Abstract: Introduction: Military personnel are reported to use more dietary supplements (DS) than the general population. However, a comprehensive investigation of DS use in Australian Army personnel has not been conducted. This study investigated the prevalence and types of DS used by Australian Army personnel and examined the underpinning reasons and demographic factors influencing this use. Materials and Methods: A Convenience sample of Australian Army personnel from both Headquarter (desk-based) and Brigade (field-based) environments completed a researcher-designed DS questionnaire. The questionnaire examined 19 types of DS (including sports foods) and reasons for use. Logistic regression, adjusting for age, sex, education, physical activity, BMI, and occupational group were performed. Results: A total of 667 personnel completed the questionnaire. Overall, 74.5% of personnel reported using ≥1 DS/day, with ~26% reporting use of ≥5 types of DS at least once/week. The most common DS used daily were caffeine (48.4%), vitamin and mineral supplements (34.8%), protein powders (27.9%), creatine (13.3%), and amino acids (13.2%). Reasons for use in descending order were "to provide energy, " "performance, " "general health, " "I like it, " "muscle gain, " "hydration, " "endurance, " "convenience, " and "weight loss." Using ≥5 DS/week was associated with a higher level of education ( p = 0.034), physical activity >10 h/week ( p < 0.0005) and having an occupation as a physical training instructor ( p = 0.040). Conclusion: If military personnel choose to utilize DS, it is important they are used in a safe, legal and effective manner. Education and up to date guidance on the rapidly evolving range of DS available are therefore necessary.